Impact of the on-site fish workshop in gaining children’s understanding and support for coastal zone management: leverage points and human-nature connection perspectives - Uehara, Takuro; Tachibana, Sawako; Hidaka, Takeshi (Frontiers in Marine Science, 2025)
Public understanding and support are essential for managing coastal zones because these are social-ecological systems (SES) in which the public plays a crucial role. As disconnection from nature may be a root cause of the unsustainability of SES, reconnecting people to nature is a promising avenue for improving their understanding and support. Although environmental education that involves exposure to nature has been considered influential in reconnecting people with nature, empirical research is lacking. Therefore, this study aimed to assess the impact of an on-site fish workshop on Japanese elementary and junior high school student’s knowledge, attitudes, intentions, and behaviors through the notion of human-nature connection (HNC) and leverage points. A 2×2 difference-in-differences design was employed in which the workshop’s impact was assessed by comparing the treatment and control groups before and after the workshop. We collected 4,054 responses, with 1,243 (pre-) and 1,088 (post-) students in the treatment group and 857 (pre-) and 866 (post-) in the control group. The preliminary findings indicate that the workshop had diverse impacts, from shallow (parameters) to deep leverage points (Information flows, Rules, Goals, and Paradigms), including HNC, support for ongoing management measures, and pro-SES attitudes and intentions. Their diverse impacts in the same direction (i.e., improvements), as found in our study, are critical because leverage points should be aligned for systemic sustainability transformation. However, changes to leverage points measured in the average treatment effect on the treated (ATET) varied from limited to extensive. Future research directions are discussed based on the preliminary findings.